Maize (Zea mays L.) Growth and Yield Response to Tillage Methods and Fertilizer Combinations in the Midland Agro-ecological Zones of Kenya - Hillary Moses Omondi Otieno; Shamie Zingore; George N. Chemining’wa; Charles K. Gachene (Turkish Journal of Agriculture: Food Science and Technology, 2020)
The trials were set up in Busia, Embu and Kirinyaga Counties to assess the effect of tillage methods and application of different fertilizer combinations on maize productivity in the lower and upper midland agro-ecological zones of Kenya. Tillage methods were no-tillage (NT) with crop residue retention as mulch (+CR) (NT+CR) and conventional tillage (CT) without crop residue retention on farm surface (-CR) (CT-CR) while fertilizer combinations were NK, NP, PK, NPK, and NPK+CaMgZnBS. The N, P, K, Ca, Mg, Zn, B and S nutrients were applied at the rates of 120, 40, 40, 10, 10, 5 and 26.3 kg ha-1, respectively. The trials were laid in a randomized complete block design with a split-plot arrangement and replicated three times. The results showed that maize leaf area index, plant height, aboveground biomass, crop growth rate, and grain yield were significantly higher under CT-CR than under NT+CR in most of the sites. The CT-CR system out-yielded NT+CR system by 0.3 t ha-1 and 0.6 t ha-1 maize grain in Alupe and Kirinyaga, respectively. However, NT+CR system out-yielded CT-CR system by 0.4 t ha -1 maize grain at Embu. Across all the sites, application of PK and NPK+ZnBMgCaS fertilizer combinations resulted, respectively, in lowest and highest maize shoot biomass, leaf area indices, crop growth rates, plant heights, and grain yields. Based on this result alone, the potential of conservation agriculture in improving yields compared to conventional tillage could not be conclusive despite consistently recording higher soil moisture content across all sites and better yields in Embu. Again, application of a wide range of nutrients may be beneficial to maize production in the study areas as evidenced in the study. Therefore, we recommend multi-season and multi-location trials to comprehensively assess the impact of tillage methods and fertilizer management, particularly in relation to micronutrients.